Mature Students' Experience: A Community of Inquiry Study during a COVID-19 Pandemic. Issue 2 (November 2022) - Homer, Damien
The COVID-19 pandemic has had a profound effect on university students across the world. In a short period of time from 2020 to 2022, Higher Education Institutions (HEIs) had to pivot their modes of delivery to ensure they could meet the needs of their students. The move to digital platforms has been challenging for students from all ages, but particularly mature students. This study sought to explore mature students' experiences of university during the COVID-19 pandemic through the lens of the Community of Inquiry (CoI) model. Utilising a qualitative approach, twenty semi-structured interviews were conducted with students from across the University of Warwick. The interviews were conducted by a staff member and a mature student during the pandemic and four themes were identified: Adapting to online learning, relationships, external factors and response of the university. This research study has identified that some participants responded well to the emergency situation, others had caring responsibilities which impacted on their studies but that peer relationships and collaborative learning is key to their success.